The effects of some educational changes in the context of reform of education goals - Maksić, Slavica; Pavlović, Zoran (Sociološki pregled, 2018)
The present study deals with the changes brought about by the educational reform since the 2001, which refer to the accomplishment of educational goals in the courses of Serbian language, religious and civic education. The study also included the analysis of the conditions in which the educational changes took place, the resources needed and prevailing social values. The results of the previous relevant studies indicate that the defined goals related to the instruction of Serbian, religious and civic education have not been accomplished in targeted level. The analysis also shows that adequate material and human resources for the reform implementation have not been provided, as well as that the prevailing values do not support the planned development of the education. It is concluded that these difficulties pose the challenges on whose overcoming the future of educational changes depends.